Treatment for Intermediate-Stage Hepatocellular Carcinoma: Current Practice and Outcome in Real World Study - Hasan, Irsan; Loho, Imelda Maria; Lesmana, Cosmas Rinaldi A.; Gani, Rino Alvani; Siregar, Lianda; Waspodo, Agus Sudiro; Lesmana, Laurentius A (The Indonesian Society for Digestive Endoscopy, 2022)
Background: Intermediate-stage hepatocellular carcinoma (HCC) is a very heterogeneous disease. The first line treatment for this group is transarterial chemoembolization (TACE), however, in clinical practice, not all patients are suitable for TACE. We aim to evaluate current treatment practice and outcome of patients with intermediate-stage HCC.Methods: HCC patients database from 2013 to 2016 in Cipto Mangunkusumo Hospital and Dharmais Cancer Hospital were retrospectively analyzed. Patients with intermediate-stage HCC were included in this study.Results: A total of 456 patients were diagnosed with HCC, but only 151 (33.1%) patients with intermediate-stage HCC were included. Men outnumbered women in a ratio of 3:1. The most common etiology for HCC was hepatitis B virus (HBV) infection, which accounted for 55% of patients. Fifty-two patients (34.4%) were treated with TACE as first-line treatment. Sixty-seven patients (44%) were given best supportive care due to ineligibility for TACE. Frequency of TACE varied from one to eleven times. Overall median survival was 617 days (1.7 years). One-year survival for patients undergoing TACE and liver resection was 47% and 60%, respectively. We did not compare the survival between any treatment groups because the number of patient in each group is not sufficient to be statistically analyzed.Conclusion: Only 34.4% of patients with intermediate-stage HCC was treated with TACE as first-line treatment. An improvement in the treatment strategy should be done for HCC patients in Indonesia.